2016
DOI: 10.1002/oby.21451
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of high‐dairy‐protein, variable‐carbohydrate diets and exercise on body composition in adults with obesity

Abstract: Objective: This study determined the effects of 16-week high-dairy-protein, variable-carbohydrate (CHO) diets and exercise training (EXT) on body composition in men and women with overweight/obesity. Methods: One hundred and eleven participants (age 47 6 6 years, body mass 90.9 6 11.7 kg, BMI 33 6 4 kg/m 2 , values mean 6 SD) were randomly stratified to diets with either: high dairy protein, moderate CHO (40% CHO: 30% protein: 30% fat; 4 dairy servings); high dairy protein, high CHO (55%: 30%: 15%; 4 dairy ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Despite this, comparable changes in body composition and cardiometabolic health were seen with post-exercise milk, milk-protein, or water. In agreement, Parr et al (2016) found changes in body composition after a combined resistance training and diet intervention were independent of the amount and type of protein (high/low dairy). Epidemiological data shows an inverse relationship between low-fat dairy consumption and the risk of type 2 diabetes (Aune et al, 2013) and the addition of four servings of low fat dairy per day has been shown to improve insulin resistance (Rideout et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…Despite this, comparable changes in body composition and cardiometabolic health were seen with post-exercise milk, milk-protein, or water. In agreement, Parr et al (2016) found changes in body composition after a combined resistance training and diet intervention were independent of the amount and type of protein (high/low dairy). Epidemiological data shows an inverse relationship between low-fat dairy consumption and the risk of type 2 diabetes (Aune et al, 2013) and the addition of four servings of low fat dairy per day has been shown to improve insulin resistance (Rideout et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…The effects of dairy on the prevention of weight gain have been previously investigated in rodents (9,10,26) and humans ; however, the mechanism (s) through which dairy reduced weight gain was not identified. For example, diet‐induced obese rats fed a HFHS diet supplemented with complete dairy protein, the same diet as used in the current study, had a greater attenuation in weight gain when compared to rats that were fed the HFHS diet with casein or whey alone as the protein source .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the combined effects of dairy and exercise in the context of weight loss. Parr et al found that dairy did not augment the effects of exercise and a hypocaloric diet on weight loss in subjects with obesity. However, it remains to be seen whether dairy can augment the effects of exercise in slowing the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…One hundred and eleven males and females aged 35–59 years began a 16-wk weight loss intervention incorporating diet and exercise modification, as previously described [ 14 ]. Prior to commencing the intervention, participants had a BMI of 27–40 kg/m 2 and were sedentary but otherwise apparently healthy.…”
Section: Methodsmentioning
confidence: 99%